ANALISIS KEPUASAN KONSUMEN DITINJAU DARI KUALITAS PELAYANAN WARUNG INTERNET REVOLUTION CYBER CAFE (RVN) MALANG - Bagus Prasetyo; Soekarto Soekarto (STIA MALANG, 2020)
This study aims to determine the level of influence of the service quality dimensions, which consist ofreliability, responsiveness, assurance, empathy, and tangible, on consumer satisfaction at the Revolution Cyber Cafecafe, which we will briefly describe as RVN in Malang,In this study using Umar's theory, the type of research is explanatory. The research location is on JalanBungur Malang. The population in this study is all customers who come and use the services of the RevolutionCyber Café (RVN) internet cafe. While the sample in this study amounted to 75 customers who came. whencarrying out this research. While the sampling technique using purpose sampling. In analyzing the data, the methodused in this study used a descriptive method and was assisted by the SPSS 20 softwareThe conclusion of this study is that there is a discrepancy between customer expectations and performanceat the internet cafe Revolution Cyber Café (RVN) Malang. There are still many items of service performance thatare lower than customer expectations, so that in general the RVN cafe still needs to evaluate performance and makeimprovements to its existing performance.Keywords: Service quality